Early Target Attainment With Continuous Infusion Meropenem and Piperacillin/Tazobactam and Utilization of Therapeutic Drug Monitoring in Critically Ill Patients: A Retrospective Cohort Study From 2017 to 2020. (20th March 2023) - Dräger, Sarah; von Rotz, Matthias; Labhardt, Niklaus D; Siegemund, Martin; Rentsch, Katharina M; Osthoff, Michael; Franzeck, Fabian C
Abstract: Background: We analyzed the attainment of early pharmacological targets of continuous infusion meropenem and piperacillin/tazobactam and the use and effect of a real-time therapeutic drug monitoring (TDM) program on subsequent dosing and target attainment in patients who are critically ill. Methods: This was a single-center, retrospective study among patients hospitalized in the intensive care unit in a Swiss tertiary care hospital from 2017 to 2020. The primary outcome was target attainment [100% t T ≥ 4xECOFF ( Pseudomonas aeruginosa ) ] of continuous infusion meropenem and piperacillin/tazobactam within 72 hours after initiation of treatment. Results: A total of 234 patients were included. Median first meropenem (n = 186 of 234) and piperacillin (n = 48 of 234) concentration was 21 mg/L (interquartile range [IQR], 15.6–28.6) and 100.7 mg/L (IQR, 64.0–160.2), respectively. Pharmacological target was attained in 95.7% (95% confidence interval [CI], 91.7–98.1) of patients receiving meropenem and 77.0% (95% CI, 62.7–87.9) treated with piperacillin/tazobactam. In the univariable and multivariable logistic regression, body weight and estimated glomerular filtration rate were negatively associated with target attainment. Subsequently, meropenem dosage was decreased or stopped in 35 of 186 (18.8%) and 89 of 186 (47.9%) patients, respectively, and increased in 2 of 186 (1.1%) patients. Conclusions: Continuous infusion meropenem and piperacillin/tazobactam yielded excellent and moderate early pharmacological target attainment in critically ill patients, respectively. The TDM was mainly used to decrease meropenem dosage. Abstract : In this observational study in critically ill patients, continuous infusion meropenem and piperacillin/tazobactam yielded excellent and moderate early pharmacological target attainment measuring antibiotic concentration in plasma.